Exploring TED talks as linked data for education. (20th April 2015) - Taibi, Davide; Chawla, Saniya; Dietze, Stefan; Marenzi, Ivana; Fetahu, Besnik
Abstract In this paper, we present the TED Talks dataset which exposes all metadata and the actual transcripts of available TED talks as structured Linked Data. The TED talks collection is composed of more than 1800 talks, along with 35 000 transcripts in over 30 languages, related to a wide range of topics. In this regard, TED talks metadata available in structured, multilingual and HTTP‐accessible form constitute a valuable resource, for instance, for schoolteachers, to explore controversial contemporary topics with their students in order to stimulate awareness and critical thinking or as a means for language learning. Moreover, being compliant with state‐of‐the‐art Linked Data principles, our dataset facilitates the computation of links with related data and resources. The TED dataset is used by a number of educational applications, and it is included in the LinkedUp Data Catalog.